Beyond time-averaged measurement of bubble parameters in steam-water flows with conductivity probes. (May 2021) - Ooi, Zhiee Jhia; Brooks, Caleb S.
Highlights: Template for reporting beyond-time averaged measurements in future datasets generated with conductivity probes. High-speed videos to show bubble behaviors and flow structures under adiabatic phase-change conditions. Distributions of bubble parameters such as duration, chord length, and velocity. Benchmark of bubble diameter distributions. Abstract: Two-phase data from flashing experiments are presented beyond the traditional time-averaged approach in this work. Probability density functions of parameters such as bubble duration, velocity, chord length, and number frequency are obtained from four-sensor conductivity probes and presented here. The axial evolution of the distributions is discussed in detail along with high-speed videos for a qualitative description of the flow field. The distributions of bubble parameters are observed to be positive-skewed with a long tail, and the shape of the distributions is analyzed in terms of the skewness and kurtosis. The number frequency of spherical and cap bubbles in the liquid slug is studied, as well as the number ratios of each bubble type in the flow. Parametric studies are carried out to investigate the effects of mass flux and system pressure on the distributions of bubble parameters. Bubble diameter distribution functions such as the Nukiyama-Tanasawa, Weibull, and lognormal distributions are validated with the chord length data of spherical bubbles where the Nukiyama-Tanasawa distribution appears to fit the chord length data the best. Sensitivity study is performed to investigate the effects of the adjusting parameters on the accuracy of the fits. The data are potentially useful for the benchmark and validation of high-fidelity simulation tools and the development of modeling approaches for phase-change flows. This work also provides a template for reporting beyond-time averaged measurements in future datasets generated with conductivity probes.